2021
DOI: 10.1186/s13071-021-04659-9
|View full text |Cite
|
Sign up to set email alerts
|

A U.S. isolate of Theileria orientalis, Ikeda genotype, is transmitted to cattle by the invasive Asian longhorned tick, Haemaphysalis longicornis

Abstract: Background Theileria orientalis is a tick-borne hemoparasite that causes anemia, ill thrift, and death in cattle globally. The Ikeda strain of T.orientalis is more virulent than other strains, leading to severe clinical signs and death of up to 5% of affected animals. Within the Asia–Pacific region, where it affects 25% of Australian cattle, T.orientalis Ikeda has a significant economic impact on the cattle industry. In 2017, T.orientalis Ikeda was detected in a cattle herd in Albermarle County… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 50 publications
2
62
0
Order By: Relevance
“…The LOD of A. marginale was a 10 -5 dilution of reference DNA, extracted from a clinically positive sample according to our in-house PCR. Although a standard curve was not run alongside this PCR assay, extrapolating from a similar assay run in our laboratory (supplementary data 8 ) suggests that 1 × 10 9 pmol of Chitose gBlock is ~16 gene copies; 10 8 pmol of Ikeda gBlock is ~25 gene copies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LOD of A. marginale was a 10 -5 dilution of reference DNA, extracted from a clinically positive sample according to our in-house PCR. Although a standard curve was not run alongside this PCR assay, extrapolating from a similar assay run in our laboratory (supplementary data 8 ) suggests that 1 × 10 9 pmol of Chitose gBlock is ~16 gene copies; 10 8 pmol of Ikeda gBlock is ~25 gene copies.…”
Section: Resultsmentioning
confidence: 99%
“…16 T. orientalis Ikeda has recently been identified in cattle in Virginia, affecting animals that were also parasitized with H. longicornis ticks 12 ; this tick has been confirmed as a competent vector in Virginia for T. orientalis Ikeda. 8 The animals that were clinically affected in this outbreak had the typical signs of anemia, icterus, and general malaise. In Virginia, this clinical presentation is identical to the blood infection caused by the bacterium Anaplasma marginale.…”
mentioning
confidence: 95%
“…The full spectrum of biological vectors (or definitive) hosts for T. orientalis has not been resolved. Amongst arthropods, the 3-host ixodid tick Haemaphysalis longicornis (Neumann, 1901) [ 38 ] has been confirmed in transmission trials as one biological vector for T. orientalis in early studies [ 8 ] in Australia [ 26 , 39 ] and the USA [ 19 ]. H. longicornis has a predicted, widespread distribution in countries with temperate climates [ 40 ], including Australia, New Zealand, Fiji, New Caledonia, China, former USSR, Korea and Japan [ 41 , 42 ], the USA, and several other Pacific Islands, including Hawaii [ 43 ].…”
Section: Features Of the Transmission And Pathogenesis Of T Orientalismentioning
confidence: 99%
“…Of these genotypes, 1 and 2 cause the majority of clinical disease in cattle in Australia [ 13 , 14 ], and elsewhere [ 5 ]. These pathogenic genotypes are recognised in many countries including Australia [ 15 ], New Zealand [ 16 ], Japan [ 17 ], Korea [ 18 ], and USA [ 19 ]. The disease has been estimated to cost the livestock industries in Japan and Korea around USD $100 million annually [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…and Hepatozoon canis), and human pathogens (e.g., Borrelia, Ehrlichia, Rickettsia, and several viruses) [6]. Recently, investigators in Virginia determined field-collected H. longicornis were infected with the Theileria orientalis Ikeda genotype and demonstrated that study ticks were competent experimental vectors for the Ikeda strain of the pathogen in local cattle [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%